METHODICAL SYSTEM OF ORGANIZATION OF THE ALGORITHMIC TESTING IN THE PROCESS OF PREPARATION OF FUTURE TEACHERS OF MATHEMATICS ﻿ - Snezhko, M.B. (Journal of Information Technologies in Education (ITE), 2010)
In the article the features of organization of control of knowledge are examined in the process of algorithmic preparation of future teachers of mathematics by facilities of IKT. As an example drawings on programmatic-methodical complexes, which are utilized for control of knowledge on algorithmization setting, functionality and architecture of the module «Library of tasks» of the integrated environment of study of course of «Basis of algorithmization and programming» (http://weboap.ksu.ks.ua), developed in the laboratory of the integrated environments of teaching of RI IT is described.